Stitch less, clip less, three ports laparoscopic cholecystectomy: experience of 300 cases - Resutra, Ritvik; Mahajan, Neha; Gupta, Rajive (International Journal of Research in Medical Sciences, 2019)
Background: 300 cases of cholelithiasis were operated by stitch less, clip less, three ports laparoscopic cholecystectomy at Maxx lyfe Hospital, near Bathindi morh, Sunjwan road, Jammu with effect from August 2017 to May 2019. The outcome measures in the form of safety of the technique, postoperative pain, need of postoperative analgesia, number of OT assistants needed, duration of hospital stay, recovery and return to routine work, cosmetic satisfaction of the patient were taken into consideration and were found to be better than in conventional four ports technique of laparoscopic cholecystectomy. Methods: In three port laparoscopic cholecystectomy, first 10 mm umbilical, second 5 mm subxyphoid and third 5 mm subcostal ports are used and telescope is passed into the peritoneal cavity through the umbilical port. Retraction of the gallbladder is done by the long grasping forceps through the 5 mm subcostal port, whereas dissection is accomplished through the subxyphoid port. The gallbladder is retrieved through the subxyphoid port. Results: Mean operative time was 40 minutes and mean duration of postoperative stay in the hospital was 18 hours. Days to return to normal activity was 4 days at an average. Conclusions: The 3-port laparoscopic cholecystectomy technique is safe and has better outcomes in the form of less postoperative pain, less duration of hospital stay, early return to routine work and more cosmetic satisfaction as compared to the conventional 4-port technique, with no obvious increase in bile duct injuries and it can be a viable alternative in the field of minimally invasive surgery.